On guidance and volatility - Billings, Mary Brooke; Jennings, Robert; Lev, Baruch (Journal of Accounting and Economics, 2015)
In contrast to theoretical and empirical evidence linking disclosure to information environment benefits, recent research concludes that guidance increases volatility, but leaves open the question of whether volatility plays a role in prompting the issuance of guidance. Consistent with the notion that managers react to rising volatility by providing guidance, we document a link between abnormal run-ups in volatility and the decision to issue a forecast after controlling for the market’s ability to anticipate the guidance. Upon disentangling pre-guidance volatility changes from post-guidance volatility changes, we find no evidence that guidance increases volatility. Indeed, our evidence consistently supports the view that managers seek to and do mitigate share price volatility with guidance.